2014
DOI: 10.1080/00986445.2014.910771
|View full text |Cite
|
Sign up to set email alerts
|

An Unreacted Shrinking Core Model for Calcination and Similar Solid-to-Gas Reactions

Abstract: A variation on the unreacted shrinking core model has been developed for calcination and similar non-catalytic solid-to-gas decomposition reactions in which no gaseous reactant is involved and the reaction rate decreases with increasing product gas concentration. The numerical solution of the model has been validated against an analytical solution for the isothermal case. The model parameters have been tuned using literature data for the thermal dehydration (calcination) of gibbsite to alumina over a wide rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 41 publications
(62 reference statements)
0
14
0
Order By: Relevance
“…forms (Amiri et al, 2013a;Amiri et al, 2015). In an effectively agitated reactor with a constant supply of CO 2 gas molecules, as reported by Linga et al, (Linga et al, 2007) hydrate formation is considered to occur in individual water droplets, and therefore the MSSCM encompassing both the nucleation and growth steps can be schematically illustrated as shown in Fig.…”
Section: Multi-stage Scm Developmentmentioning
confidence: 96%
See 1 more Smart Citation
“…forms (Amiri et al, 2013a;Amiri et al, 2015). In an effectively agitated reactor with a constant supply of CO 2 gas molecules, as reported by Linga et al, (Linga et al, 2007) hydrate formation is considered to occur in individual water droplets, and therefore the MSSCM encompassing both the nucleation and growth steps can be schematically illustrated as shown in Fig.…”
Section: Multi-stage Scm Developmentmentioning
confidence: 96%
“…Solid-fluid models are another approach to model the process of gas hydrate formation. The unreacted shrinking core model (SCM), in particular, has been commonly used for modelling of gas-solid reactions in which the diffusion rate is slow compared to the reaction rate on the unreacted core (Amiri et al, 2015). It has been shown that diffusion in the hydrate layer, in contrast to the mass transfer in the fluid surrounding the particle, is the most dominant controlling mechanism for the overall progress of CO 2 hydration (Dashti et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical modelling of gas-solid systems is usually used to interpret experimental results and to gain insight into the reaction mechanisms. Due to its importance, the modelling of these heterogeneous reactions has been of strong interest to investigators for several decades, resulting in a variety of modelling approaches [16]. The major models that have been developed for non-catalytic gas-solid reactions are the unreacted shrinking core, shrinking particle, homogeneous and grain models.…”
Section: Reduction Roasting Kineticsmentioning
confidence: 99%
“…Kinetic decomposition was studied by applying unreacted shrinking core model [17]. The influence of different temperature regions upon the thermal behavior of chemical compounds can provide kinetic parameters indicating change in the reaction pathway.…”
Section: Introductionmentioning
confidence: 99%